2003
DOI: 10.1042/bst0311075
|View full text |Cite
|
Sign up to set email alerts
|

Regression of pre-established atherosclerosis in the apoE−/− mouse by conjugated linoleic acid

Abstract: Conjugated linoleic acid (CLA) refers to a group of positional and geometric isomers of linoleic acid that has been shown to suppress the development of atherosclerosis in a rabbit model. We investigated whether CLA acts as a cyclo-oxygenase (COX) inhibitor or as an agonist of the peroxisome-proliferator-activator receptor (PPAR) gamma in the ApoE(-/-) mouse model. In vitro, a 9-cis, 11-trans isomer of CLA inhibited prostaglandin formation and oxygen consumption by both isoforms of COX, with no evidence by MS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
9

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 52 publications
0
31
0
9
Order By: Relevance
“…Studies in cell cultures have demonstrated protective properties (8,11,15,38). In animals, these properties can be observed while using either the CLA isomeric mixture (cis-9,trans-11-and trans-10,cis-12-CLA, 50:50) (17,37) or selected CLA isomers (cis-9,trans-11-or trans-10,cis-12-CLA) (16,32). In most studies, these fatty acids consistently attenuate the formation of primary vascular lesions (fatty streaks) or induce regression of preestablished lesions (16,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in cell cultures have demonstrated protective properties (8,11,15,38). In animals, these properties can be observed while using either the CLA isomeric mixture (cis-9,trans-11-and trans-10,cis-12-CLA, 50:50) (17,37) or selected CLA isomers (cis-9,trans-11-or trans-10,cis-12-CLA) (16,32). In most studies, these fatty acids consistently attenuate the formation of primary vascular lesions (fatty streaks) or induce regression of preestablished lesions (16,17).…”
mentioning
confidence: 99%
“…Although present in minor amounts in diets, CLA has been receiving growing interest for its multiple health-related effects reported in various animal models (35). Especially, the antiatherogenic properties of CLA are now supported by many animal studies in rabbits (16), mice (32), and hamsters (37). Studies in cell cultures have demonstrated protective properties (8,11,15,38).…”
mentioning
confidence: 99%
“…The doses used in our studies were based on previous published works. 19,20 Urine was collected overnight in metabolic cages; blood samples were obtained by retro-orbital bleeding from animals fasted overnight, as previously described. 9,10 …”
Section: Animals and Experimental Protocolsmentioning
confidence: 99%
“…It has been shown to exhibit in animal studies beneficial health effects on cancer prevention and treatment, and cardiovascular risk (reviewed by Wahle et al (2004)). Chemically synthesised CLA (cis-9, trans-11 CLA or mixture of cis-9, trans-11 þ trans-10, cis-12 CLA) have been shown to protect against the development and progression of atherosclerosis in rabbits (Kritchevsky et al, 2002 and2004), hamsters (Nicolosi et al, 1997;Wilson et al, 2000) and ApoE-KO mice (Toomey et al, 2003) when a pro-atherogenic diet was fed. Moreover, the addition of a cis-9, trans-11 CLA-rich mixture to butter depressed some risk factors of CVD in cholesterol-fed hamsters (Valeille et al, 2005).…”
Section: Introductionmentioning
confidence: 99%